Anteseden Kecurangan Akuntansi - Asbi Amin; Muslim Muslim; Novita Adam; Rapika Anwar; Parmin Ishak (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
The phenomenon of fraud in Indonesia often involves people who have important positions in an organization, including the Makassar City regional apparatus organization where in the 2018-2020 period several findings of fraud were revealed. This study detects how compensation and compliance with accounting rules affect accounting fraud and wants to test whether strict accounting rules through moderating unethical behavior affect accounting fraud. The research sample is 92 Apparatus in Makassar City Regional Apparatus Organizations. Data were collected from distributed questionnaires and tested using the Partial Least Square (PLS) approach. We find that compensation and accounting compliance have a significant negative influence on accounting fraud. Unethical behavior is able to moderate the relationship between compliance with accounting rules and accounting fraud.